Annual ADEA Survey of Dental School Seniors: 2014 Graduating Class. Issue 9 (1st September 2015) - Wanchek, Tanya; Cook, Bryan J.; Anderson, Eugene L.; Valachovic, Richard W.
Abstract : This study presents the results of the annual American Dental Education Association (ADEA) Survey of Dental School Seniors for the graduating class of 2014. Where appropriate, data from past surveys are incorporated to show changes over time. The survey covers a range of topics, including students' decisions to pursue a dental career, dental school experience, financing of dental education, planned activities after graduation, and perceived preparation to treat underserved groups. The survey response rate was 84% and included respondents from all 58 U.S. dental schools with graduating classes in 2014. The findings characterize who is entering the dental profession, how they will contribute to the dental workforce, and whether schools are meeting the perceived needs of students. Following graduation, these seniors reported primarily planning to enter private practice (45%) or advanced dental education (38%). Of those going into private practice, 65% planned to be an associate at a private dental practice. Nearly 11% had no educational debt, while the remaining respondents averaged 247, 227 in total educational debt. Although few seniors intended to teach immediately after graduation, over half planned to teach at some point in the future. Finally, most of these seniors reported that their schools had generally met their perceived needs; agreed or strongly agreed that the time spent on most subject areas was appropriate; and agreed or strongly agreed that their school's curriculum had adequately prepared them to practice in settings with culturally and ethnically diverse patients. Among the demographic findings were that a quarter of the seniors were from lower income families. These students were more likely to have become interested in dentistry as a career prior to undergraduate studies than did the higher income students. These and other results from the survey provide a look into the experiences and perceptions of new dental professionals.